Biliary, pancreatic or duodenal cancer in carriers of biliodigestive anastomoses previous due to non-neoplastic pathology - Praderi, Raúl C; Harretche, Martín; Chiossoni, Martha; Retich, Gisela; Navarrete, Héctor; Beguiristain, Alberto; Gutiérrez Galiana, Horacio; Juambeltz, Nelson; Iacopino, Julio; Dutto, Gabriel; et al. (Cirugía del Uruguay, 1992)
The authors present the clinical histories of tour patients; three of them had been operated on because of biliary lithiasis by other surgeons. Two of the ones with choledochal stones had been treated by means of choledocho–duodenostomy and years la ter one developed cancer of the choledochus and the other duodenal cancer. The patient whose choledochus was bound underwet a hepato-jejunostomy and was readmitted the fol/owing year with cancer of the pancreas head which obviously did not resu/t in jaundice.